Using thermodynamics to obtain geochemical information from genomes. Issue 2 (14th November 2022) - Dick, Jeffrey M.; Boyer, Grayson M.; Canovas, Peter A.; Shock, Everett L.
Abstract: Thermodynamic characterization of the relative stabilities of chemical compounds is a pillar of conceptual models in various fields of geosciences. Analogous models applied to genomes can yield new information about the relationship between genomes and their geochemical environments. In this perspective article, we present a chemical and thermodynamic analysis of prokaryotic lineages that have been the target of previous phylogenomic studies of evolutionary adaptation to varying redox conditions. The thermodynamic model development begins by quantifying the effects of hydrogen activity ( a H2 ) and temperature on the relative stabilities of organic compounds with different carbon oxidation state. When applied to proteins instead of metabolites, the same techniques can be used to identify combinations of a H2 and temperature at which reference proteomes for Class I or Class II methanogens are relatively stable. The calculated a H2 values are compatible with reported measurements for habitats of methanogens ranging from highly reducing submarine hydrothermal systems to less reducing environments including methanogenic sediments. In contrast to the transition between the two classes of methanogenic archaea, that between basal and terrestrial groups of Thaumarchaeota (denoting the origin of ammonia‐oxidizing archaea) occurs at a less‐reducing redox boundary. These examples reveal the consequences of energy minimization driving evolution and show how geochemical calculations involving biomolecules can be used to quantify and better understand the coevolution of the geosphere and biosphere.